Latent Impact of Groundwater Exploitation by "PT X" from the Perspective of Green Criminology - Desti Desita; Monica Margaret (Dinasti International Journal of Education Management And Social Science, 2024)
Klaten has the nickname of the city of a thousand umbul, with good water quality making Klaten a place for AMDK companies to operate. This research aims to describe the latent impact of groundwater exploitation carried out by PT X based on the perspective of green criminology. Green criminology highlights various phenomena that have an impact on the environment and the interests of the wider community. With the rise of AMDK (Bottled Drinking Water) companies in the Klaten Regency area, it certainly has a lot of impact on the environment and the surrounding community. Various protests have been filed by the community in the hope that the community's interest in water for their agricultural land can be considered. This research was conducted using a qualitative method with data collection techniques through interviews with all parties involved, observation, and literature study. The data collected will be studied using the perspective of green criminology. The results of this research are expected to provide a new understanding for the wider community about how the impact caused by excessive exploitation of groundwater. It is also expected that the community can take part in the process of conserving groundwater so that the amount of groundwater supply.